An Image Encryption and Text Encryption Scheme Based on an Elliptic Curve using Montgomery Curve and Haga’s function - Aqil, Muhammad; Ahmad, Mukhtar; Qayyum, Ather; Alsulami, Ibrahim K.; Fakhrou, Abdulnaser; Atta, Gulnaz (Discontinuity, Nonlinearity, and Complexity, 2026)
The internet is gradually becoming a riskier medium of communication for all types of highly sensitive information. Individuals, institutions, and organizations greater reliance on the internet to conduct business processes has created a fertile ground for intruders to launch various attacks on the system and network. The security of crucial secret information such as personal identifying information, credit card details, online transactions, and e-commerce is of the utmost importance, and it is dependent on cutting-edge cryptography. The article proposes an alternative cryptography algorithm based on mathematical objects known as elliptic curves. In this paper, firstly a new text encryption technique is described in which a private key can be created using the Haga’s theorem. Secondly, a new image encryption technique that makes use of specific functions such as the Haga’s function and the Montgomery Curve is introduced. The proposed algorithm’s effectiveness is verified by experimental testing and the usage of modern security tools. The simulation results and comparison of the proposed approach to existing image encryption algorithms show that it provides a sufficient level of security.